A propósito de la mitología shipibo - Bertrand-Rousseau, Pierrette (1984)
Based on two texts collected by the author, she elaborates a literary review of the adventures of Cori-lnca, the hero of order, and Yoashico-Inca, the anti-hero, the founder of the rebellions, of the great transformations.